Sucesso escolar no Espaço Cooperativo de Aprendizagem Horizonte: perspectivas de estudantes multirrepetentes e seus professores - Busatte, Flávia Camargo (Universidade Federal de São Carlos, 2024)
The present study addresses the investigation of the school experiences of students experiencing educational lag, enrolled in 2023 at the Horizonte Learning Cooperative Space (ECAH), a project of the Poços de Caldas Municipal Department of Education, MG:aiming to identify elements that may contribute to the academic success of these students. To this end, the following research question was proposed: What are the elements present in Espaço Cooperativo de Aprendizagem Horizonte (ECAH) that have the potential to promote academic success of students with a history of academic failure? In order to answer this question, the following objectives were proposed: (a) Identify the ECAH elements that can stimulate the academic success of students with a history of academic failure, considering their previous difficulties. (b) Understand these students’ academic experiences in order to identify relevant elements that may contribute to their education improvement, with academic success as the central objective. (c) Analyze how ECAH addresses and work on these issues, identifying pedagogical practices, strategies, and elements that favor the academic success of participating students, especially those with challenges stemming from past academic failures. The research methodology was a qualitative case study, and data collection techniques included group discussions and semi- structured interviews with ECAH’s both students and teachers. The theoretical-methodological principles of Paulo Freire’s theory were considered, highlighting the importance of dialogue, pedagogical praxis, and emancipation in education, used as analysis categories. The students’ statements during group discussions and interviews, as well as the teachers’ expressions in interviews were used to establish relations between ECAH’s experiences outlined by theses voices and Paulo Freire’s theory. This study found that it is essential to establish an educational environment conducive to participation of both students and teachers in the sharing of knowledge, valuing reciprocal experiences. The adoption of a problem-posing approach is recommended, in which relevant topics for the students are critically explored. Furthermore, reflection is encouraged in line with action, enabling students to apply their learning to transform their reality. It is concluded that these elements form an interconnected network that guides the pursuit of quality education and social transformation, being fundamental to promote academic success and the emancipation of individuals.
School success in the Horizonte Cooperative Learning Space: perspectives of multi-repeating students and their teachers
Keywords: Sucesso escolar; Paulo Freire; Dialogicidade; Afetividade; Práxis; Emancipação; School success; Dialogicity; Affectivity; Praxis; Emancipation; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO